Health status of people with autism spectrum disorder - Koceski, Antonio; Trajkovski, Vladimir (Emerald Publishing, 2021)
Purpose The aim of this study is to determine what changes occur in the health status of people with ASD compared to neurotypical controls. Design/methodology/approach We performed a comparative analysis of data collected from 72 subjects with ASD and 75 neurotypical controls aged 3-24 years using the Rochester Health Status Survey IV (RHSS-IV). A structured individual interview was conducted to compare the health status of subjects in Macedonia. Findings The majority of people with ASD take vitamins, supplements and use recommended drug therapies compared to the neurotypical population and experience a larger number of side effects (p=0.000). Compared to people with neurotypical development, children with ASD have a higher prevalence of oral ulcers (31.9% vs. 17.3%; p=0.039), changes in neurological health status- epilepsy (19.4% vs. 2.7%; p=0.001) and ADD/ADHD (only persons with ASD-19.4%; p=0.000); respiratory diseasesangina (30.5% vs. 8%; p=0.000), rhinitis and / or sinusitis (40.3% vs. 17.3%; p=0.02); changes in the gastrointestinal system- constipation (31.9% vs. 10.6%; p=0.02), intestinal inflammation (19.4% vs. 8%; p=0.043), permeable intestines (only persons with ASD - 13.9%; p=0.000) and the presence of the fungus Candida albicans (19.4% vs. 4%; p=0.043); psychiatric disorders- sleep problems (only in people with ASD - 18%; p=0.000) and tics (6.9% vs. 2.6%; p=0.25), and skin diseaseseczema/allergic skin rash (36.1% vs. 18.7%; p=0.02). Originality Many children with ASD have health problems. These findings support and complement the professional literature on their mutual causality.
Здравствена состојва кај луѓето со аутистичен спектар на нарушување
Keywords: autistic spectrum disorder, health status, disease